Simulação computacional de materiais bidimensionais: funcionalização de defeitos extensos no grafeno e retenção de contaminantes por argilominerais - Lima, Felipe David Crasto de (2016)
In this work are considered two bidimensional systems, with distints chacacteristcs and applicabilitys. Is studied the adsorption of transition metals (MT) Fe, Co, Mn and Ru in extended defects, formed by graphene grain boundaries. First in pristine graphene The hollow site of carbon hexagon, in pristine graphene, are the most stable for MT adsorption. The Dirac cone in eletronic structure of graphene was manteined with the presence of MT. For the considered grain boundaries the MT has a greater stability for absorption in the grain boundaries sites in comparison with pristine graphene. Through the energy barrier values, are observed diffusion chanels for MT localized on the grain boundaries. This diffusion chanels indicate a possible formation of nanolines of MT in graphene. For the first stage of the nanolines, ate observed a better stability for the system with greater MT concentration, due to MT-MT interactions. Also, due to the magnetic moment of the MT, the nanolines show a magnetization. For the most stable configurations the system are metallics, particularly for Fe the band structure indicates an anisotropic spin current. In a second study, are considereted the retention capacity for metallic contaminants Cd and Hg in clayminerals, kaolinite (KAO) and montmorillonite (MMT). Through the adsorption energies of contaminantes in the clayminerals, was observed a increase in stability with the increase of contaminants concentration, due to the interaction Cd-Cd and Hg-Hg. Also, was observed that KAO has a strong interaction beteween monolayers than MMT. In this sence, for the adsoption process of contaminantes in the natural form of KAO and MMT, the latter has a better retention capacity, due to the small net work for contaminant intercalation. However, when the modification of clayminerals, with molecules that increase the spacing between monolayers, exist a optimal condition, which the contaminant absorption are more stable in KAO system than in MMT. In the Langmuir adsorption model for the clayminerals in the optimal monolayer spacing, the retention capacity for Cd and Hg in KAO system are 21% greater than in MMT system. Also, for the X-ray Absorption Near Edge Spectroscopy (XANES) for the K edge of Cd and Hg, are found a positive shift of absorption edge with the decreasing of monolayer spacing. This result indicates a possible way to determine the concentration of adsorbed contaminats in relation to unabsorbed ones, from the decomposition of experimental XANES in the obteined spectras.